Synthesis, Antifungal and Antitumor Activity of Novel (Z)-5-Hetarylmethylidene-1,3-thiazol-4-ones and (Z)-5-Ethylidene-1,3-thiazol-4-ones (2013)
New hetaryl- and alkylidenerhodanine derivatives 3a-d, 3e, and 4a-d were prepared from heterocyclic aldehydes 1a-d or acetaldehyde 1e. The treatment of several rhodanine derivatives 3a-d and 3e with piperidine or morpholine in THF under reflux, afforded (Z)-5-(hetarylmethylidene)-2-(piperidin-1-yl) thiazol-4(5H)-ones and 2-morpholinothiazol-4(5H)-ones 5a-d, 6a-d, and (Z)-5-ethylidene-2-morpholinothiazol-4(5H)-one (5e), respectively, in good yields. Structures of all compounds were determined by IR, 1D and 2D NMR and mass spectrometry. Several of these compounds were screened by the U.S. National Cancer Institute (NCI) to assess their antitumor activity against 60 different human tumor cell lines. Compound 3c showed high activity against HOP-92 (Non-Small Cell Lung Cancer), which was the most sensitive cell line, with GI(50) = 0.62 mu M and LC50 > 100 mu M from the in vitro assays. In vitro antifungal activity of these compounds was also determined against 10 fungal strains. Compound 3e showed activity against all fungal strains tested, but showed high activity against Saccharomyces cerevisiae (MIC 3.9 mu g/mL).